Di Balik Topeng Penderitaan: Telaah Etis Teologis Atas Dramaturgi Pura-Pura Miskin - Saputra, Andi; Stefanus, Yohanes; Zebua, Arwani (Jurnal Ilmiah Wahana Pendidikan, 2026)
This study examines the phenomenon of “pretending to be poor” through an ethical-theological approach using dramaturgical theory from Erving Goffman. The focus lies on identity distortion, violations of honesty and love, and their implications for social justice and church diaconal practices. This research employs a qualitative library method with descriptive-interpretative and hermeneutical analysis. The findings reveal that this phenomenon reflects a rupture in human relationships with God, others, and self, and calls for the renewal of Christian ethics and diakonia grounded in integrity, verification, and holistic empowerment.